Dapagliflozin is associated with lower risk of cardiovascular events and all‐cause mortality in people with type 2 diabetes (CVD‐REAL Nordic) when compared with dipeptidyl peptidase‐4 inhibitor therapy: A multinational observational study. Issue 2 (8th September 2017) - Persson, Frederik; Nyström, Thomas; Jørgensen, Marit E.; Carstensen, Bendix; Gulseth, Hanne L.; Thuresson, Marcus; Fenici, Peter; Nathanson, David; Eriksson, Jan W.; Norhammar, Anna; Bodegard, Johan; Birkeland, Kåre I.
Abstract : Aims: To compare the sodium‐glucose‐cotransporter‐2 (SGLT‐2) inhibitor dapagliflozin with dipeptidyl peptidase‐4 (DPP‐4) inhibitors with regard to risk associations with major adverse cardiovascular (CV) events (MACE; non‐fatal myocardial infarction, non‐fatal stroke or cardiovascular mortality), hospitalization for heart failure (HHF), atrial fibrillation and severe hypoglycaemia in patients with type 2 diabetes (T2D) in a real‐world setting. Methods: All patients with T2D prescribed glucose‐lowering drugs (GLDs) during 2012 to 2015 were identified in nationwide registries in Denmark, Norway and Sweden. Patients were divided into two groups: new users of dapagliflozin and new users of DPP‐4 inhibitors, matched 1:3 by propensity score, calculated by patient characteristics, comorbidities and drug treatment. Cox survival models were used to estimate hazard ratio (HR) per country separately, and a weighted average was calculated. Results: After matching, a total of 40 908 patients with T2D were identified as new users of dapagliflozin (n = 10 227) or a DPP‐4 inhibitor (n = 30 681). The groups were well balanced at baseline; their mean age was 61 years and 23% had CV disease. The mean follow‐up time was 0.95 years, with a total of 38 760 patient‐years. Dapagliflozin was associated with a lower risk of MACE, HHF and all‐cause mortality compared with DPP‐4 inhibitors: HRs 0.79 (95% confidence interval [CI] 0.67‐0.94), 0.62 (95% CI 0.50‐0.77), and 0.59 (95% CI 0.49‐0.72), respectively. Numerically lower, but non‐significant HRs were observed for myocardial infarction (0.91 [95% CI 0.72‐1.16]), stroke (0.79 [95% CI 0.61‐1.03]) and CV mortality (0.76 [95% CI 0.53‐1.08]) Neutral associations with atrial fibrillation and severe hypoglycaemia were observed. Conclusions: Dapagliflozin was associated with lower risks of CV events and all‐cause mortality compared with DPP‐4 inhibitors in a real‐world clinical setting and a broad T2D population.